Assertive Training in the Form of Role- Playing to Control the Aggressive Behavior of People with Schizophrenia in the Community - Nihayati, Hanik Endang; Kadji, Ramona Irfan; Rachmawati, Praba Diyan; Yusuf, Ah; Fitryasari, Rizki; Tristiana, Dian; Yunita, Fildzah Cindra (International Journal of Psychosocial Rehabilitation, 2020)
Schizophrenics are significantly linked to violent behavior compared to those with other disorders. There is an inextricable link between mental illness and violence, creating stigma and an uncomfortable environment for the family. This study aimed to analyze the ef ect of role-playing on the ability to control the anger of schizophrenics with violent behavior in the community. The design of this study was quasi- experimental with a pre-test-post-test control group design. The sample was divided into 2 groups consisting of 18 participants in the control group and 18 participants in the treatment group. The Federer formula and purposive sampling method was used to determine the sample size. The data collection was accumulated by observation on a pre-test and post-test sheet. The data was analyzed using a Paired and Independent T-Test (p< 0,05). The results of the ability to control anger in the treatment group experienced an increase after being given assertive training (role-playing) (p=0.000) while there was no dif erence (p=0.097) in the control group in accordance with the results of the research which showed assertive training was proven to improve the anger control ability of schizophrenics with violent behavior in Lawang Psychiatry Hospital. Using assertiveness training, especially role-playing, can decrease anger. This method will improve their anger management skill and help the nurses in preventing the recurrence of violent behavior among schizophrenics.